Alpha1 antitrypsin deficiency due to an homozygous PI* Null Q0Cairo mutation: Early onset of pulmonary manifestations and variability of clinical expression. (2018) - Jouhadi, Zineb; Odou, Marie Francoise; Zerimech, Farid; Bousfiha, Ahmed Aziz; Mikou, Nabiha; Porchet, Nicole; Crepin, Michel; Najib, Jilali; Balduyck, Malika
Abstract: Alpha-1 antitrypsin deficiency is an autosomal, codominant disorder caused by mutations of the SERPINA1 gene. This genetic disorder is mainly associated with development of pulmonary emphysema and/or chronic liver disease and cirrhosis. Here we report a very rare alpha-1 antitrypsin Null Q0cairo homozygous mutation characterized by a complete absence of alpha-1 antitrypsin in the plasma, in a non-consanguineous Moroccan family. This mutation has been previously described in heterozygosis in only three cases worldwide: an Italian/Egyptian family and two Italian families (Zorzetto et al., 2005). The main clinical features in two members of this Moroccan family were the severity and precocity of bronchiectasis, quickly spreading and seriously limiting respiratory function and physical activity by the second decade of age. Moreover, the index case presented with many episodes of pulmonary infections concomitant with severe neutropenia. The third member of the family presented with ankylosing spondyloarthritis and developed panniculitis later but had no respiratory symptoms. The presence of this alpha-1-antitrypsin Q0cairo homozygous mutation could explain the severity of clinical manifestations. Moreover, our observations highlight a great variability of clinical expression for the same mutation: early severe bronchiectasis, panniculitis, rheumatologic manifestations. This study further underlines the importance of genotyping by whole SERPINA1 gene sequencing in addition to serum alpha-1 antitrypsin determination, to enable detection of alpha-1 antitrypsin deficiency due to rare genotypes.